EFEKTIVITAS MODEL PEMBELAJARAN MANDIRI MENGGUNAKAN MODUL DIGITAL DAN MODUL CETAK TERHADAP HASIL BELAJAR SEJARAH DITINJAU DARI MINAT BACA SISWA - Muhimatunnafingah, Siti; Herimanto, Herimanto; Musadad, Akhmad Arif (Program Studi Pendidikan Sejarah FKIP Unversitas Sebelas Maret, 2018)
The purpose of this study was to determine: 1) The effectiveness difference of the self-directed learning use digital module and printed module on the students' learning achievement of history. 2) The effectiveness difference of the self-directed learning use digital module and printed module on the learning achievement students of history who have a high read interest. 3) The effectiveness difference of the self-directed learning use digital module and printed module on the learning achievement students of history who have a low read interest. 4) The interaction effect between the use of the self-directed learning and interest in read on the learning achievement of history.This research used experimental methods. The population in this study were all students of class XI SMA Negeri 1 Surakarta 2017/2018 school year with 2 sample that is class XI IPS 1 consisted of 23 students and XI IPS 2 consisted of 25 students drawn by cluster random sampling technique. Techniques of collecting data using questionnaires and test methods that have been tested with validity and reliability testing. Data was analyzed by two-way analysis of variance with 2x2 factorial design.Based on the result of research it appear that: (1) There is a significant effectiveness difference between use the self-directed learning use digital module and printed module to students' learning achievement history (probability value < significance level = 0,001<0.05), (2) There is a significant effectiveness difference between use the self-directed learning use digital module and printed module on the learning achievement of students of history who have a high read interest (probability value < significance level = 0,037<0.05), (3) There is not significant effectiveness difference between use the self-directed learning use digital module and printed module on the learning achievement of students of history who have a low read interest (probability value < significance level = 0,182>0.05), and (4) There is no interaction effect between the use of the self-directed learning and interest in read on the learning achievement of history. (probability value < significance level = 0,629>0.05).